Skin Exposure to Narrow Band Ultraviolet (UVB) Light Modulates the Human Intestinal Microbiome - Bosman, Else S.; Albert, Arianne Y.; Lui, Harvey; Dutz, Jan P.; Vallance, Bruce A. (Frontiers in Microbiology, 2019)
The recent worldwide rise in idiopathic immune and inflammatory diseases such as multiple sclerosis and inflammatory bowel diseases has been linked to Western society-based changes in lifestyle and environment. These include decreased exposure to sunlight/UVB light and subsequent impairment in the production of vitamin D, as well as dysbiotic changes in the makeup of the gut microbiome. Despite their association, it is unclear if there are any direct links between UVB light and the gut microbiome. In this study we investigated whether exposing the skin to Narrow Band Ultraviolet B (NB-UVB) light to increase serum vitamin D levels would also modulate the makeup of the human intestinal microbiota. The effects of NB-UVB light were studied in a clinical pilot study using a healthy human female cohort (n=21). Participants were divided into those that took vitamin D supplements throughout the winter prior to the start of the study (VDS+) and those who did not (VDS-). After three NB-UVB light exposures within the same week, the serum 25(OH)D levels of participants increased on average 7.3 nmol/L. The serum response was negatively correlated to the starting 25-hydroxy vitamin D (25(OH)D) serum concentration. Fecal microbiota composition analysis using 16S rRNA sequencing showed that exposure to NB-UVB significantly increased alpha and beta diversity in the VDS- group whereas there were no changes in the VDS+ group. Bacteria from several families were enriched in the VDS- group after the UVB exposures according to a Linear Discriminant Analysis prediction, including Lachnospiracheae, Rikenellaceae, Desulfobacteraceae, Clostridiales vadinBB60 group, Clostridia Family XIII, Coriobacteriaceae, Marinifilaceae, and Ruminococcus. The serum 25(OH)D concentrations showed a correlation with the relative abundance of the Lachnospiraceae, specifically members of the Lachnopsira and Fusicatenibacter genera. This is the first study to show that humans with low 25(OH)D serum levels display overt changes in their intestinal microbiome in response to NB-UVB skin exposure and increases in 25(OH)D levels, suggesting the existence of a novel skin-gut axis that could be used to promote intestinal homeostasis and health. Clinical trial registration: clinicaltrials.gov, NCT03962673. Registered 23 May 2019 - Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT03962673?term=NCT03962673&rank=1